Rantai Pasok Halal Minuman Herbal dalam Mendukung Sustainabilitas Bisnis di UMKM Jelly Barokah Genteng Surabaya - Nurlailah, Nurlailah; Rahmawati, Lilik; Ali Mustofa, Imam (Program Studi Ilmu Ekonomi UIN Sunan Ampel Surabaya, 2024)
This study aims to determine the halal supply chain of herbal drinks in supporting business sustainability (implementation at MSME Jelly Barokah Genteng, Surabaya) through field studies. This research uses a qualitative approach. Research data collection techniques through field studies and documentation. Field studies were conducted through observation and interviews. The halal supply chain is used to indicate the halalness of a product in terms of starting from the production preparation process, production process, to the distribution process. In this study, it was found that the MSMEs of Jelly Barokah herbal drinks have been certified halal MUI east Java Province and meet the halal supply chain in the production of their products. The implementation of the 3P aspect, namely the profit aspect, the people aspect, and the planetary aspect in the halal supply chain of herbal beverage products from Jelly Barokah MSMEs, aims to maintain the sustainability of their business. The purpose of implementing 3P also means that the production of herbal drinks from MSMEs Jelly Barokah is not only based on the profits of MSME owners, but the production of each herbal drink product is also reviewed from the aspects of the community around MSME actors and aspects of the surrounding environment